Surface free fat bridging contributes to the stickiness of powdered infant formula milk pasteurized by radio frequency dry heat treatment. (June 2022) - Zhang, Yue; Xie, Yongkang; Chen, Yiting; Pandiselvam, Ravi; Liu, Yanhong
Abstract: The effects of radio frequency (RF) dry heat treatment on powdered infant formula milk (PIFM) stickiness were investigated. Commercial spray-dried PIFM with a water activity of 0.28 was treated at a constant temperature of 70 °C for 0, 23.3, 46.6, 69.9, 93.2, and 116.5 min, corresponding to 0–5 logarithmic inactivation of Cronobacter sakazakii . All RF treatments significantly reduced the water activity, while induced insignificant change in lactose crystallinity (∼2%–3%) and surface free fat content (∼0.005–0.006 g/g powder) compared with the untreated sample. The particle size of PIFM was increased markedly when the holding time reached 23.3 min, and after that changed insignificantly, suggesting that the stickiness between neighboring particles was completed at the initial stage of pasteurization. The stickiness of the powders was noted along with the flow of molten surface fat when processed for 23.3 min, but fat coverage decreased due to fat solidification as time increased from 23.3 min to 116.5 min. Compared with the untreated samples, the increased surface lactose coverage of treated PIFM reduced the critical water activity for glass transition from 0.39 to 0.31 at 25 °C. This study demonstrated that surface free fat bridges were responsible for increasing particle size after RF dry heat pasteurization. Highlights: Radio frequency treatment redistributed the surface free fat. Surface fat bridge contributed to a significant increase in particle size. Radio frequency distinctly increased the lactose exposure on the particle surface. Radio frequency reduced the critical water activity for lactose glass transition.